Von Kant zu Schelling. Die beiden Wege des Deutschen Idealismus - Vető, Miklós (De Gruyter, 2019)
The classic work on German idealism is now presented in the translation by Hans-Dieter Gondek. Miklós Vető's text provides an analysis of the four principal philosophers of German idealism, with an emphasis on the issues of metaphysics, morality, and the philosophy of religion.